Organic Zinc as Feed Additive for Ruminants - ., Suprijati (Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Zinc is an essential micro mineral required by ruminants and is a component of over 300 enzymes which play important role in the metabolisms of carbohydrates, proteins and fats. Recently, the chemical and biotechnology processes have been developed for synthesizing organic Zn. Organic Zn is the product of a chelating process of dissolved Zn anorganic salts with amino acids or hydrolyzed protein. The utilization of organic Zn as feed additive in ruminants diets tends to increase, due to the absorption  of Zn  in  the  organic  form is  more  effective  than  the  inorganic  form.  This  paper  reviewes  the  research  from comparative studies of inorganic and organic Zn on the growth, production and reproduction in ruminants. The studies found that the supplementation of organic Zn improved nutrient digestibility, growth, feed efficiency, milk production, Zn retention and absorption, production and reproductive performances of ruminants. However, a little variation response was found due to different degrees of chelating on Zn incorporation of amino acids or hydrolyzed protein.   Key words: Organic Zn, characteristic, supplementation, performance, ruminants